DDD and DU90% Analysis of Antimicrobial Therapy of Community-Acquired Pneumonia in the In-Patient Department of the Federal Center - O. V. Zhukova; O. V. Ruina; S. V. Kononova; M. V. Khazov; S. V. Romanov (Антибиотики и Химиотерапия, 2020)
The purpose of the study Is to conduct DDD analysis and DU90% analysis of antimicrobial therapy of community-acquired pneumonia in the real clinical practice of the inpatient department of the federal center in Russia. Material and methods. The materials for the study are data from 48 case histories of patients with CAP, hospitalized in the Volga District Medical Centre (VDMC) under Federal Medical and Biological Agency (FMBA) of Russia in Nizhny Novgorod in 2016. The patients' age ranged from 22 to 84 years (54.79+17.49). The diagnosis was confirmed by x-ray examinations at admission. The average severity of the disease was diagnosed in 41.67% (20 patients), the severe degree of the disease in 58.33% (28 patients). When conducting a retrospective pharmacoepidemiological assessment, DDD analysis and DU90% analysis were used. Results. The largest number of prescriptions falls on III generation cephalosporins and fluoroquinolones. The largest NDDD value corresponds to levofloxacin, followed by ceftriaxone (NDDD = 108.5 g, which is 4.3 times less than for levofloxacin). Within the framework of 100 bed-days in the hospital, 69.67% of patients receive levofloxation therapy, which is several times greater than the proportion of patients receiving therapy with other antimicrobial agents. The group constituting 90% of all the NDDD antimicrobial drugs consumed in CAP included: levofloxacin - 71.19%, ceftriaxone - 16.50%, ertapenem - 4.70%. The DU10% segment was comprised of medications with the share in the real structure of prescriptions amounting to 24.56%. The cost of one DDD in the DU90% segment (6,022.88 rubles) is 1.9 times higher than that in the DU10% segment (3,166.73 rubles), which allows discussing the extensive use of expensive drugs. Conclusions. Drugs, included in the group of 90% according to the results of DU90%, accounted for 75.44% in the real purpose structure. Expensive antimicrobials (original drugs and high-quality generics) were predominantly used in the hospital. The cost of one DDD in the DU90% segment is almost 2 times the cost of DDD in the DU10% segment.